A narrative review of the literature on the reproductive health of female sex workers having age below twenty years (Bangladesh Journal of Medical Science, 2019)
Objective: Female sex workers (FSWs) under 20 years of age range from 1,000 to 575,000 in different cities and countries across the globe. There is only a handful of information on the reproductive health (RH) issues of these younger FSWs in the perspective of service utilization and healthcare system. We reviewed existing literature with a view to describe the reproductive health problems, service utilization, and service availability as well as information sources among the FSWs ages